Fasudil Dichloroacetate Alleviates SU5416/Hypoxia-Induced Pulmonary Arterial Hypertension by Ameliorating Dysfunction of Pulmonary Arterial Smooth Muscle Cells - Liu P; Huang W; Ding Y; Wu J; Liang Z; Huang Z; Xie W; Kong H (Dove Medical Press, 2021)
Ping Liu,1,* Wen Huang,1,* Yirui Ding,1 Jianbing Wu,2 Zhuangzhuang Liang,2 Zhangjian Huang,2 Weiping Xie,1 Hui Kong1 1Department of Respiratory and Critical Care Medicine, The First Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu, 210029, People’s Republic of China; 2State Key Laboratory of Natural Medicines, China Pharmaceutical University, Nanjing, 210009, People’s Republic of China*These authors contributed equally to this workCorrespondence: Weiping Xie; Hui KongDepartment of Respiratory and Critical Care Medicine, The First Affiliated Hospital of Nanjing Medical University, 300 Guangzhou Road, Nanjing, Jiangsu, 210029, People’s Republic of ChinaTel +86-25-68136426Fax +86-25-68136269Email wpxie@njmu.edu.cn; konghui@njmu.edu.cnBackground: Pulmonary arterial hypertension (PAH) is an incurable disease that urgently needs therapeutic approaches. Based on the therapeutic effects of fasudil and dichloroacetate (DCA) on PAH, we aimed to explore the effects and potential mechanism of a new salt, fasudil dichloroacetate (FDCA), in a SU5416 plus hypoxia (SuHx)-induced rat model of PAH.Methods: The rat model of PAH was established by a single subcutaneous injection of SU5416 (20 mg/kg) followed by hypoxia (10% O2) exposure for 3 weeks. FDCA (15, 45, or 135 mg/kg i.g. daily) or the positive control, bosentan (100 mg/kg i.g. daily), were administered from the first day after SU5416 injection. After 3-week hypoxia, hemodynamic parameters, and histological changes of the pulmonary arterial vessels and right ventricle (RV) were assessed. Additionally, in vitro, the effects of FDCA (50 μM), compared with equimolar doses of fasudil, DCA, or fasudil+DCA, on the proliferation, migration, and contraction of human pulmonary arterial smooth muscle cell (PASMC) under hypoxia (1% O2) were evaluated.Results: FDCA dose-dependently attenuated SuHx-induced PAH, with significant reductions in RV systolic pressure, pulmonary artery wall thickness, pulmonary vessel muscularization, perivascular fibrosis, as well as RV hypertrophy and fibrosis. In vitro, FDCA inhibited hypoxia-induced PASMC proliferation, migration, and contraction to a greater degree than fasudil or DCA alone by restoring mitochondrial function, reducing intracellular Ca2+, and inhibiting calcium/calmodulin-dependent kinase (Ca2+/CaMK) activity as well as Rho-kinase activity.Conclusion: FDCA ameliorates hypoxia-induced PASMC dysfunction by inhibiting both Ca2+/CaMK and Rho-kinase signaling pathways, as well as maintaining mitochondrial homeostasis, thus alleviating SuHx-induced PAH.Keywords: pulmonary arterial hypertension, fasudil dichloroacetate, pulmonary arterial smooth muscle cells, hypoxia, calcium